Supervision of the Waste Management in Bandung City - Rosana, Mira; Achdiat, Achdiat; Marisa, Mega; Tania, Nadya (Journal of Governance, 2024)
The city of Bandung is the main contributor to Citarum River pollution due to human behavior. The waste problem, both in water and on land, has not been managed properly until the end of December 2023, including the Sarimukti landfill burning incident. The increasing amount of waste makes management problems increasingly complex. Bandung City Regional Regulation no. 9 of 2018 Article 5 states that the Regional Government is responsible for ensuring the planning, organization, implementation and supervision of waste management in a sustainable and environmentally sound manner. Supervision in waste management is very important for the success of the city government in maintaining cleanliness. To prevent errors in programs or policies, supervision is needed as a success factor. This research aims to determine and analyze the implementation of the supervisory function in waste management as well as describe the inhibiting factors and efforts made in waste monitoring in Bandung City. The method used is descriptive qualitative, with data collection through interviews, observation and documentation. The validity of the data was obtained by triangulation and data analysis using John Saldana's manual coding technique by means of coding, categories and themes. The sampling technique used is accidental sampling. This research is planned to last for eight months. It is hoped that the research results will produce a concept and implementation of waste management supervision by the Bandung City Environmental Service, fulfilling TKT 2.